Moringa oleifera Lam. (Moringaceae) grown in Nigeria: In vitro antisickling activity on deoxygenated erythrocyte cells - Olufunmilayo E Adejumo; Adelodun L Kolapo; Akintomiwa O Folarin (Wolters Kluwer Medknow Publications, 2012)
Context: Traditional medicine, which is more available and affordable for the poor uses medicinal plants for the treatment and management of various ailments, including the sickle cell disease (SCD). About 24 million Nigerians are carriers of this sickled cell gene, while approximately 2.4 million are SCD patients. Moringa oleifera Lam. (Moringaceae) possesses high nutritional value and has been used in folklore medicine to treat various ailments related to pain and inflammation. Chemical, pharmacological and pharmacognostical applications of Moringa oleifera have been reported. Objective: This study investigated the antisickling potential of polar and non-polar extracts of the seed, flower and leaf of Moringa oleifera for the first time. Materials and Methods: Using crude methanol extract, aqueous extract, ethyl acetate and butanol, the in vitro antisickling activities of Moringa oleifera fractions, were evaluated using erythrocyte cells deoxygenated with 2% sodium metabisulphite. p-Hydroxybenzoic acid and normal saline were employed as positive and negative controls. Results: Phytochemical screening revealed the presence of saponins, free anthraquinones, and alkaloids. Extracts of the seed and flower demonstrated a higher (P<0.05) antisickling activity in comparison to the leaf extract. The leaf extract, as well as those of the seed and flower, equally demonstrated a (P<0.05) reversal of sickled erythrocytes. Discussions and Conclusions: These findings suggest that Moringa oleifera may play a role in the management of SCD, by incorporation of its fractions into recipes. More extensive biological evaluations and further studies will be necessary for the chemical characterization of the antisickling principles.